The Effect Of Original Regional Income And General Allocation Funds On Capital Expenditure of Central Sulawesi Province The Year 2015-2019 - Abdul Latif; Andi Mardiana; St. Aisyah (Trunojoyo University of Madura, 2022)
This study mainly aims, first, to find out the significant evidence of the effect of local revenue on capital expenditures in Central Sulawesi Province, Second, to understand the significant evidence of general allocation funds' effect on capital expenditures in Central Sulawesi Province, Third, to analyze the significant evidence of local revenue and general allocation funds simultaneously on capital expenditure in Central Sulawesi Province. The type of research used is quantitative data. Funds used in this research are secondary data provided by the Directorate General of Fiscal Balance (www.djpk.kemenkeu.go.id) by making Central Sulawesi Province which consists of 13 districts and municipality into the area under study. The results showed partial hypothesis testing that, first, Local Own Income (X1) has no significant effect on Capital Expenditures (Y). Second, General Allocation Fund (X2) has no significant effect on Capital Expenditure (Y). Meanwhile, the simultaneous hypothesis testing results show that Local Own Revenue (X1) and General Allocation Fund (X2) have a significant effect on Capital Expenditure (Y). Keywords: Regional Original Income, General Allocation Fund, Capital Expenditure